Surgical Biopsy in Cervical Lymphadenopathy - Salwan Yousif Hanna Bede; Auday M. Al-Anee; Hassanien A. Aljumaily (College of Dentistry/ University of Baghdad, 2016)
Background: Cervical lymph nodes are the most frequently enlarged and biopsied of all the peripheral lymph nodes and in most of the cases the enlargement results from benign infectious causes, however, the presence of cervical lymphadenopathy (LAP) requires accurate diagnosis to exclude more serious causes. The aim of this study was to analyze cases of Iraqi patients presenting with cervical LAP who underwent surgical lymph node biopsy to establish accurate diagnosis. Materials and Methods: This retrospective study included 25 patients who presented with cervical LAP for whom surgical biopsy was performed to establish a definitive diagnosis. The investigated data included the demographic and clinical parameters in addition to the final histopathological diagnosis. Results: Twenty five patients were included in this study with a mean age of 33.8 years and female predominance; benign diseases were diagnosed in 56% of the cases whereas the remaining 44% were diagnosed with malignant diseases. Tuberculous lymphadenitis was the most common cause. Conclusion: This study emphasizes the importance of surgical lymph node biopsy in establishing a definitive diagnosis in patients presenting with cervical LAP.